Motivation Matters: Exploring Its Impact on Students' Problem-Solving Abilities in Number Theory - nia_jusniani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This research aims to find out how student learning motivation influences problem solving abilities in number theory courses. This research uses quantitative methods with simple regression analysis. The population in the study were students of the Mathematics Education Study Program, FKIP, Suryakancana University. The subjects of this research consisted of 30 level II and level III students from the Mathematics Education Study Program, FKIP, Suryakancana University. Data collection in this research was questionnaire sheets and test sheets in the form of descriptions. The questionnaire was used to determine students' learning motivation, while the test the researchers used aimed to measure the level of students' problem solving abilities. The results of the research explain that student learning motivation does not have a significant influence on problem solving abilities in the Number Theory course.